Developmental trajectories of event related potentials related to working memory - Barriga-Paulino, Catarina I.; Rodríguez-Martínez, Elena I.; Arjona, Antonio; Morales, Manuel; Gómez, Carlos M. (Neuropsychologia, 2017)
Working memory is an important cognitive function, and it is crucial to better understand its neurophysiological mechanisms. The developmental trajectories of the Event Related Potentials related to this important function have hardly been studied. However, these ERPs may provide some clues about the individual state of maturation, as has been demonstrated for anatomical brain images. The present study aims to determine the behavioral and neurophysiological development of Working Memory (WM) processes. For this purpose, 170 subjects with ages ranging from 6 to 26 years performed a visual Delayed Match-to-Sample task (DMTS). The RTs, total errors, and Event Related Potentials (ERPs) in the phases of encoding, retention, and matching were obtained. Results revealed a decrease in the amplitude of ERPs with age, paralleled by improved performance on the DMTS task (i.e., shorter RTs and fewer errors). None of these variables were affected by gender. To determine whether memory performance was influenced by the individual pattern of maturation beyond age, the amplitude of the different ERP components was correlated with RT and errors on the WM task after removing the effect of age. Frontal N2 and posterior P1 and the Late Positive Component were the only ERPs that presented significant correlations with behavioral errors. Behavioral performance was predicted by age and by the scores on the first component extracted from Principal Component Analysis (PCA) of the ERPs. Age (under 17 years old) explained 85.04% and the PCA component explained 14.96% of the variance explained by the bivariate model predicting behavioral errors (1/age + scores of 1st PCA component). From the age of 17 on, the principal PCA component ceases to be an independent component predicting error performance. The results suggest that the individual maturation of ERP components seems to be of particular importance in controlling behavioral errors in WM, as measured by the DMTS. •All the ERPs related to Working Memory during development were analyzed.•All ERPs presented a reduction in amplitude with age.•Frontal N2, posterior P1 and the Late Positive Component are important for controlling errors,•Individual brain maturation influences cognitive performance in the 6–17 year old period.